Defining impact of a rapid response team: qualitative study with nurses, physicians and hospital administrators. Issue 5 (2nd March 2012) - Benin, Andrea L; Borgstrom, Christopher P; Jenq, Grace Y; Roumanis, Sarah A; Horwitz, Leora I
Abstract : Objective: The objective of this study was to qualitatively describe the impact of a Rapid Response Team (RRT) at a 944-bed, university-affiliated hospital. Methods: We analysed 49 open-ended interviews with administrators, primary team attending physicians, trainees, RRT attending hospitalists, staff nurses, nurses and respiratory technicians. Results: Themes elicited were categorised into the domains of (1) morale and teamwork, (2) education, (3) workload, (4) patient care, and (5) hospital administration. Positive implications beyond improved care for acutely ill patients were: increased morale and empowerment among nurses, real-time redistribution of workload for nurses (reducing neglect of non-acutely ill patients during emergencies), and immediate access to expert help. Negative implications were: increased tensions between nurses and physician teams, a burden on hospitalist RRT members, and reduced autonomy for trainees. Conclusions: The RRT provides advantages that extend well beyond a reduction in rates of transfers to intensive care units or codes but are balanced by certain disadvantages. The potential impact from these multiple sources should be evaluated to understand the utility of any RRT programme.